2013
DOI: 10.1097/tp.0b013e318275a322
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Improves Immunosuppressant Induced Hyperglycemia and Exocrine Apoptosis in Rats

Abstract: This is the first study to show that metformin can improve immunosuppressant-induced hyperglycemia, when administered concurrently, and reduces exocrine apoptosis (reducing the impact on potential islet progenitor cells).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Animal studies confirmed that treatment with tacrolimus worsened glucose tolerance both in vivo and in vitro and in normal as well as insulin-resistant models, predominantly through decreasing insulin secretion (54,55). We have shown that short-term tacrolimus treatment of normal male and female Sprague-Dawley rats caused hyperglycemia with mild hyperinsulinemia in response to glucose challenge in a dose-dependent manner, suggesting mild insulin resistance; with longer duration of treatment, hyperinsulinemia was no longer observed, suggesting loss of insulin secretion (37,54). Tacrolimus was also shown to reduce ␤-cell mass and increase islet apoptosis, but it had less impact on insulin signaling, suggesting that its predominant action was on insulin production (56).…”
Section: Role Of Immunosuppression Agentsmentioning
confidence: 58%
See 3 more Smart Citations
“…Animal studies confirmed that treatment with tacrolimus worsened glucose tolerance both in vivo and in vitro and in normal as well as insulin-resistant models, predominantly through decreasing insulin secretion (54,55). We have shown that short-term tacrolimus treatment of normal male and female Sprague-Dawley rats caused hyperglycemia with mild hyperinsulinemia in response to glucose challenge in a dose-dependent manner, suggesting mild insulin resistance; with longer duration of treatment, hyperinsulinemia was no longer observed, suggesting loss of insulin secretion (37,54). Tacrolimus was also shown to reduce ␤-cell mass and increase islet apoptosis, but it had less impact on insulin signaling, suggesting that its predominant action was on insulin production (56).…”
Section: Role Of Immunosuppression Agentsmentioning
confidence: 58%
“…However, there are few studies to demonstrate whether these medications can prevent PTDM. In animal studies, metformin can minimize immunosuppressant-induced hyperglycemia (54), and rosiglitazone prevents hyperglycemia secondary to sirolimus (210). However, the potential side effects of thiazolidinediones (eg, edema, heart failure, and bone loss) reduce enthusiasm for their use as a diabetes prevention agent in any transplant group.…”
Section: Prevention Of Ptdmmentioning
confidence: 99%
See 2 more Smart Citations
“…Metformin inhibits mitochondrial respiration and activates AMP-activated protein kinase (AMPK) resulting in decreased hepatic gluconeogenesis and decreased insulin resistance resulting in lower blood glucose levels. It has already been demonstrated that metformin reduces sirolimus/tacrolimus-induced hyperglycaemia in rats, highlighting its possible efficacy in treatment-induced insulin resistance [93]. In a clinical trial in paediatric acute lymphoblastic leukaemia (ALL) patients metformin lowers steroid-induced hyperglycaemia with an acceptable side-effect profile [94].…”
Section: Diabetes Medication To Treat Therapy-induced Insulin Resistancementioning
confidence: 99%